Implementasi Pengatur Suhu Dalam Water Heater: Meningkatkan Efisiensi Energi dan Keamanan - Firdaus, Muhamad Lutfi; Milah, Muhamad Zainal; Rahayu A. N., Rintan; Fuadin, Ahmad (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This article focuses on the temperature control sensor in a water heater which has a very important role in maintaining the performance, safety and efficiency of the device. This sensor is responsible for monitoring the water temperature in the tank and controlling the heating element so that the temperature remains at the desired setting. The advantages of using temperature control technology in water heaters emphasize the importance of aspects of operational safety and efficient energy use. The aim of this research is to implement temperature control, involving elements such as thermometers, thermostats and microcontrollers, with a focus on optimizing the operational conditions of the Water Heater. The research method used is experimental research, the data collection process involves several stages to observe and measure the effects of implementing temperature control technology on Water Heaters starting from Installing a Temperature Controller, Measuring Temperature and Energy Consumption, Data Analysis by installing a temperature controller on the Water Heater and carry out statistical analysis of the collected data. The research results show significant improvements in operational safety, reducing the risks associated with excessive water heating. Apart from that, the efficiency of energy use has also increased, making the implementation of temperature control a way to improve Water Heater performance. Thus, the results of this research not only improve operational safety but also contribute to a new innovation in energy efficiency, which creates an integrated solution for daily warm water needs.